The elements - Emsley, John. (Oxford [Oxfordshire] : Clarendon Press ; New York : Oxford University Press, 1989)
Reference book containing the most important facts about all the chemical elements arranged in alphabetical order.
Includes bibliographical references (pages 7-8) and index.
Keywords: Chemical elements -- Handbooks, manuals, etc; Chemistry; Chemical elements; Chemistry - general; Subject-specific reference works; Handbook; handbooks; manuals (instructional materials); Handbooks and manuals; Handbooks and manuals; Guides et manuels